2007
DOI: 10.1111/j.1540-5915.2007.00172.x
|View full text |Cite
|
Sign up to set email alerts
|

Competitive and Cooperative Positioning in Supply Chain Logistics Relationships*

Abstract: Cooperative logistics relationships require the sharing of information, which must be enabled by the integration of disparate information systems across partners. In this article, we theorize business-to-business logistics relationships should be managed using cooperative and competitive postures. Based on data from 91 dyadic relationships using interorganizational information technology (IT), we find that performance gains accrue when parties share strategic information and customize IT; mutual trust enables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
148
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(166 citation statements)
references
References 104 publications
7
148
0
Order By: Relevance
“…Alternatively, Firm A is already cognizant that IT can lead to improvements in strategic information flow, opportunities to make data driven decisions and ultimately reduced transaction costs [62], expecting that tracking technology will further all of these gains.…”
Section: Technology Integrationmentioning
confidence: 99%
“…Alternatively, Firm A is already cognizant that IT can lead to improvements in strategic information flow, opportunities to make data driven decisions and ultimately reduced transaction costs [62], expecting that tracking technology will further all of these gains.…”
Section: Technology Integrationmentioning
confidence: 99%
“…The main argument for information sharing is the reduction in the transaction costs and the uncertainty (Tan et al, 2010). On the contrary, partners may prefer to withhold sensitive information to diminish the threat of opportunism (Klein et al, 2007). In this case, the information is considered an asset that requires additional safeguarding mechanisms (Kembro et al, 2014).…”
Section: Transaction Cost Economics (Tce) Hostage Modelmentioning
confidence: 99%
“…In this case, the information is considered an asset that requires additional safeguarding mechanisms (Kembro et al, 2014). Therefore, it may lead to unwillingness to invest into highly specific IOSs (Tan et al, 2010;Klein et al, 2007).…”
Section: Transaction Cost Economics (Tce) Hostage Modelmentioning
confidence: 99%
“…This allows comparisons to be made between companies of different size (Lusch and Brown, 1996). Profitability was initially formulated based on Kaynak (2002), Narasimhan and Kim (2002), and Han (2009), whereas competitive performance was initially formulated based on Narasimhan and Kim (2001), and Straub et al (2007). These items have been employed to jointly measure the construct of 'profitability & competitive performance' .…”
Section: Chaptermentioning
confidence: 99%
“…It was found that trading partners' level of trust in the client positively influenced their information exchange behavior, and in turn, information communication positively affected client customizations (Klein et al, 2007). Trust was also found to be an important factor influencing the adoption and use of inter-organizational information systems Saunders, 1997, 1998;Gang et al, 2006).…”
mentioning
confidence: 99%